2016
DOI: 10.1002/ente.201600184
|View full text |Cite
|
Sign up to set email alerts
|

Development, Status, and Prospects of Coal Tar Hydrogenation Technology

Abstract: China is rich in coal resources, and the production of mid‐to‐low‐temperature coal tar is increasing gradually. Due to containing more aliphatic hydrocarbons and less aromatic hydrocarbons, mid‐to‐low‐temperature coal tar is suitable for hydrogenation to produce fuel oil. Domestic mid‐to‐low‐temperature coal tar hydrogenation technologies are investigated here. All the technologies are divided into 6 steps, that is, coal tar hydrogenation technology of the light fraction, the delayed coking tar, the suspending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…The >360 • C heavy distillate fraction (distillation residue) accounted for about half mass of the total MLCT, which belongs to coal tar pitch (mainly composed of polycyclic aromatic hydrocarbons), and was the main component of the MLCT. Researches [7,8,36,37] have shown that the >360 • C heavy distillate fraction is exceedingly difficult to hydrogenate and has a low economic value. Figure 3 shows the elemental composition analysis of the narrow distillate fractions.…”
Section: Hydrocarbon-group-type Analysismentioning
confidence: 99%
“…The >360 • C heavy distillate fraction (distillation residue) accounted for about half mass of the total MLCT, which belongs to coal tar pitch (mainly composed of polycyclic aromatic hydrocarbons), and was the main component of the MLCT. Researches [7,8,36,37] have shown that the >360 • C heavy distillate fraction is exceedingly difficult to hydrogenate and has a low economic value. Figure 3 shows the elemental composition analysis of the narrow distillate fractions.…”
Section: Hydrocarbon-group-type Analysismentioning
confidence: 99%
“…At the same time, they also determine that the system mainly use a peer-to-peer network called the P2P network. The P2P network has the characteristics of decentralization, scalability, and load balancing [4]. These characteristics can conveniently manage the nodes participating in the system's function spreading throughout the world, and therefore they are widely used in the entire blockchain system.…”
Section: Core Networking Modementioning
confidence: 99%
“…But in the coming decades, fossil fuels will continue to provide more than 85% of global energy consumption. Compared with oil and natural gas, the attraction of coal lies in its abundant reserves and stable prices . Therefore, the efficient use of coal is increasingly paramount to the sustainable development of the world economy and society.…”
Section: Introductionmentioning
confidence: 99%